2018
DOI: 10.1001/jamapediatrics.2018.1492
|View full text |Cite
|
Sign up to set email alerts
|

Association of In Utero Exposure to Polybrominated Diphenyl Ethers With the Risk of Hypospadias

Abstract: IMPORTANCE Polybrominated diphenyl ethers (PBDEs) are added to many consumer products as flame retardants, and their endocrine-disrupting properties are a growing health concern in pregnancy.OBJECTIVE To investigate whether in utero PBDE exposure as measured in maternal hair is associated with increased risk for hypospadias. DESIGN, SETTING, AND PARTICIPANTSIn this case-control study, the setting was the urology clinic of a tertiary pediatric hospital between January 3, 2011, and April 1, 2013. Participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…An increase in gestational age was supported by Chen et al [98], but Eick et al [94] and Jin et al [91] observed a negative association with PBDE exposure. Additionally, there were other studies that did not find statistically significant associations between neonatal health indices and PBDE exposure levels [109,110] or found associations that were incomparable to the results from our selection of studies, such as associations with hypospadias in neonates [111,112]. The conflicting results could have been due to the differences in confounder adjustments, the statistical analyses used, multiple chemical exposures, congener profiles, and the study design.…”
Section: Reproductive Healthmentioning
confidence: 62%
“…An increase in gestational age was supported by Chen et al [98], but Eick et al [94] and Jin et al [91] observed a negative association with PBDE exposure. Additionally, there were other studies that did not find statistically significant associations between neonatal health indices and PBDE exposure levels [109,110] or found associations that were incomparable to the results from our selection of studies, such as associations with hypospadias in neonates [111,112]. The conflicting results could have been due to the differences in confounder adjustments, the statistical analyses used, multiple chemical exposures, congener profiles, and the study design.…”
Section: Reproductive Healthmentioning
confidence: 62%
“…Gestational exposure to eight PBDEs was measured in mothers of boys diagnosed with hypospadias. Total PBDE levels were significantly higher (up to 48%) among mothers of infants with hypospadias than among controls ( Koren et al, 2019 , Poon et al, 2018 ). A similar study found that maternal PBDE levels were not significantly different between women with infants with hypospadias and women with unaffected infants, however only 20 hypospadias infants were included in this study ( Carmichael et al, 2010 ).…”
Section: Edcs Associated With Hypospadiasmentioning
confidence: 84%
“…Twice more risk of infants developing cryptorchidism was observed with every ten times increase in the concentration of BDE-99, BDE-100 or BDE-154 in the maternal hair [29]. Similarly, higher levels of total PBDE and five individual congeners 47,99,153,and 154) were found in the hair of mothers whose infants had hypospadias (n = 152) than among controls (n = 64) in Toronto [30,31]. In multivariable model, hypospadias was associated with a relative 48.2% (95% CI, 23.3%-65.4%) higher maternal hair level of total PBDE including 8 congeners (Poon et al, 2018).…”
Section: Reproductive Health Studies In Humansmentioning
confidence: 92%